Contemporary Co-housing in Europe Towards Sustainable Cities? - Hagbert, Pernilla; Larsen, Henrik Gutzon; Thörn, Håkan; Wasshede, Cathrin (Taylor & Francis, 2020)
This book investigates co-housing as an alternative housing form in relation to sustainable urban development. Co-housing is often lauded as a more sustainable way of living. The primary aim of this book is to critically explore co-housing in the context of wider social, economic, political and environmental developments. This volume fills a gap in the literature by contextualising co-housing and related housing forms. With focus on Denmark, Sweden, Hamburg and Barcelona, the book presents general analyses of co-housing in these contexts and provides specific discussions of co-housing in relation to local government, urban activism, family life, spatial logics and socio-ecology. This book will be of interest to students and researchers in a broad range of social-scientific fields concerned with housing, urban development and sustainability, as well as to planners, decision-makers and activists.